1995
DOI: 10.1002/jlac.199519950114
|View full text |Cite
|
Sign up to set email alerts
|

Teil‐ und perfluorierte Thioketone und Thioaldehyde Chemische Speicherung, in‐situ‐Freisetzung und ungewöhnliche 1,3‐dipolarophile Reaktivität gegenüber Bis(trimethylstannyl)diazomethan (BTSD) und C,N‐Bis(triisopropylsilyl)nitrilimin (NI)

Abstract: Partially and Perfluorinated Thioketones and Thioaldehydes: Chemical Storage, In Situ Generation and Surprising Reactivity towards Bis(trimethylstanny1)-diazomethane (BTSD) and C,N-Bis(triisopropylsily1)nitrilimine (NI)The hetero-Diels-Alder anthracene adducts la-d are synthesized in a one-pot reaction from the corresponding partially and perfluorinated carbonyl compounds in good yields. By their thermolysis in solution in presence of BTSD or NI the 1,3-dipolar 1:l cycloadducts 12a, d, 14a, b, d are obtained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…The CI, MALDI, and FAB ϩ mass spectra also failed to produce a molecular ion signal for 6. Fluorinated thioketones have been found to react with diazobis(trimethylstannyl)methane to form unsymmetrical azines [11] in a manner unrelated to our present observations. Huisgen et al [12] have reported the two-step, head-to-head symmetrical dimerization of diphenylmethanethione Smethylide 7 Ǟ 8 (Scheme 4), but this still means that our unsymmetrical dimerization of 5, with one molecule acting as a 1,3-dipole and the other as a 1,3-dipolarophile (Scheme 2), is unprecedented.…”
Section: Resultscontrasting
confidence: 43%
“…The CI, MALDI, and FAB ϩ mass spectra also failed to produce a molecular ion signal for 6. Fluorinated thioketones have been found to react with diazobis(trimethylstannyl)methane to form unsymmetrical azines [11] in a manner unrelated to our present observations. Huisgen et al [12] have reported the two-step, head-to-head symmetrical dimerization of diphenylmethanethione Smethylide 7 Ǟ 8 (Scheme 4), but this still means that our unsymmetrical dimerization of 5, with one molecule acting as a 1,3-dipole and the other as a 1,3-dipolarophile (Scheme 2), is unprecedented.…”
Section: Resultscontrasting
confidence: 43%
“…Compound 12b affords d,l -1,2-bis(trimethylsilyl)-1,2-ethanedithiol on reduction and trans -2,3-bis(trimethylsilyl)thiirane and trans -1,2-bis(trimethylsilyl)ethene on photolysis . Other sulfines have recently been reported to dimerize to 1,2-dithietane 1,1- dioxides …”
Section: Resultsmentioning
confidence: 99%